Análise do processo de implantação do balanced scorecard: o caso do painel corporativo de uma empresa brasileira do setor público - Arantes, Gisella Reis de (2006)
Lately it has been observed a great interest around the literature on management tools. During the nineties there was a euphoria around Total Quality Management (TQM), a large adoption of Reengineering along with Outsourcing and core-competencies management Based on academic research, the Balanced Scorecard (BSC) emerged in the early nineties and rapidly it was accepted and adopted as management tool by several companies around the world. That recent utilization of BSC has led to the questioning of how well this new management tool is being adopted. The objective of this research lS to analyze the adoption of the BSC as a management tool in a Brazilian public sector organization. The results showed that the motivation for choosing the BSC and its implementation were perfectly aligned with the BSC proposed methodology. Also two unexpected results emerged from this research: first a possible key factor of success in BSC adoption that was not found in the revised literature; and second a certain peculiarity in the adoption of BSC as management tool in public sector organizations.